Development and preliminary evaluation of the Chinese adult dietary behavior scale - Zhang, Haiyue; Li, Xinrui; Wang, Yuan; Zhang, Wei; Liang, Ying; Wang, Yue; Yang, Zhe; Tan, Zhijun; Xu, Junrong; Shang, Lei (Frontiers in Nutrition, 2025)
BackgroundThere is currently no widely accepted multidimensional tool to assess adult dietary behaviors in China. This study developed the Chinese Adults Dietary Behavior Scale (CADBS) to evaluate Chinese adults’ eating-related traits and preliminarily examined its reliability, validity, and ability to distinguish different groups.MethodsThe scale was developed through three rounds of surveys conducted from 2020 to 2021. Items were screened using item analysis. After item selection, exploratory and confirmatory factor analyses were used to determine the final structure of the scale, and its reliability, structural validity, and discriminative ability were assessed accordingly.ResultsThe final scale consisted of 7 dimensions with 39 items: snacking, food responsiveness, emotional eating, restrictive eating, food fussiness, healthy dietary awareness, and external eating. Exploratory factor analysis showed a total cumulative variance contribution rate of 60.60%. Confirmatory factor analysis yielded a Tucker–Lewis index (TLI) of 0.892 and a comparative fit index (CFI) of 0.903. The total scale had a Cronbach’s α coefficient of 0.890, a split-half reliability coefficient of 0.920, and a test–retest reliability coefficient of 0.740. Snacking (β = 0.422), food responsiveness (β = 0.412), and restrictive eating (β = 0.675) were positively associated with BMI, while healthy dietary awareness (β = −0.396) was negatively associated with BMI.ConclusionFollowing standard procedures, this study developed a self-report scale for assessing Chinese adults’ dietary behaviors. The CADBS has good reliability and structural validity, making it suitable for epidemiological surveys of dietary behaviors and public health intervention practices. Specifically, it shows that Chinese adults who snack more have stronger food responsiveness and are more likely to be overweight or obese. Conversely, an overweight or obese Chinese adult tends to be restrictive about eating. On the contrary, those with greater healthy dietary awareness are more likely to have a normal weight.